Longitudinal Analysis of COVID-19 Patients Shows Age-Associated T Cell Changes Independent of Ongoing Ill-Health - Townsend, Liam; Dyer, Adam H.; Naughton, Aifric; Kiersey, Rachel; Holden, Dean; Gardiner, Mary; Dowds, Joanne; O’Brien, Kate; Bannan, Ciaran; Nadarajan, Parthiban; Dunne, Jean; Martin-Loeches, Ignacio; et al. (Frontiers in Immunology, 2021)
Objectives The trajectory of immunological and inflammatory changes following acute COVID-19 infection are unclear. Immunological changes associated with persistent symptoms following resolution of initial infection, termed long COVID, are also unclear. We investigate immunological changes in convalescent COVID-19 and interrogate their potential relationships with persistent symptoms. Methods We performed paired immunophenotyping at initial SARS-CoV-2 infection and convalescence (n=40, median 68 days) and validated findings in 71 further patients at median 101 days convalescence. Results were compared to 40 pre-pandemic controls. Fatigue and exercise tolerance were assessed as cardinal features of long COVID using the Chalder Fatigue Scale and 6-minute-walk test. The relationships between these clinical outcomes and convalescent immunological results were investigated. Results We identify persistent expansion of intermediate monocytes, effector CD8+, activated CD4+ and CD8+ T cells, and reduced naïve CD4+ and CD8+ T cells at 68 days, with activated CD8+ T cells remaining increased at 101 days. Patients >60 years also demonstrate reduced naïve CD4+ and CD8+ T cells and expanded activated CD4+ T cells at 101 days. Ill-health, fatigue, and reduced exercise tolerance were common in this cohort. These symptoms were not associated with immunological changes. Conclusion We demonstrate myeloid recovery but persistent T cell abnormalities in convalescent COVID-19 patients more than three months after initial infection. These changes are more marked with age and are independent of ongoing subjective ill-health, fatigue and reduced exercise tolerance.